Emotion Control Education in the New Normal Era Through Riyadlah Dhikr - Hasbiyallah Hasbiyallah; Faznah Faznah; Arum Ningsih (Jurnal al-Thullab, 2022)
The COVID-19 pandemic has attacked the fabric of human life. However, activities must continue, including in the field of education. This event is known as the "New Normal". In the educational environment, especially in Islamic boarding schools, there is one problem that arises, namely the lack of stable emotional control of students caused by fear and worry about the COVID-19 virus. This is because they are far from their families and have to start adapting to the new learning system. This study aimed to determine the relationship between remembrance activities and emotional control of the students of the Annida Al-Islamy Islamic Boarding School in the new normal era. In this study, a quantitative approach was used, with the correlational method. Data collection techniques were carried out by giving questionnaires to 60 students, interviews, and documentation. The results of the research are: (1) The activity of remembrance at the Annida Al Islamy Islamic Boarding School in the new normal era is categorized as high; (2) The emotional control of students is categorized as strong; (3) The relationship between the two is highly correlated. Pandemi COVID-19 telah menyerang tatanan kehidupan manusia. Akan tetapi, aktivitas harus tetap berjalan, termasuk juga di dalamnya bidang pendidikan. Peristiwa ini dikenal dengan istilah “New Normal”. Dalam lingkungan pendidikan, khususnya di pesantren terdapat salah satu masalah yang timbul yakni kurang stabilnya pengendalian emosi santri yang disebabkan rasa takut dan khawatir terhadap virus COVID-19. Hal ini dikarenakan keadaan mereka yang jauh dari keluarga serta harus mulai beradaptasi dengan sistem pembelajaran baru. Penelitian ini ditujukan untuk mengetahui adanya hubungan antara aktivitas riyadlah zikir dengan Pendidikan pengendalian emosi santri Pondok Pesantren Annida Al-Islamy di era new normal. Pada penelitian ini digunakan pendekatan kuantitatif, dengan metode korelasional. Teknik pengumpulan data dilakukan dengan memberikan angket kepada 60 santri, wawancara, dan dokumentasi. Hasil penelitian yang didapat adalah: (1) Aktivitas zikir di Pondok Pesantren Annida Al Islamy pada era new normal berkategori tinggi; (2) Pengendalian emosi santri berkategori kuat ; (3) Hubungan antara keduanya berkorelasi tinggi.